Intravital imaging with two-photon microscopy reveals cellular dynamics in the ischeamia-reperfused rat heart. Issue 1 (December 2018) - Matsuura, Ryohei; Miyagawa, Shigeru; Fukushima, Satsuki; Goto, Takasumi; Harada, Akima; Shimozaki, Yuri; Yamaki, Kazumasa; Sanami, Sho; Kikuta, Junichi; Ishii, Masaru; Sawa, Yoshiki
Abstract Recent advances in intravital microscopy have provided insight into dynamic biological events at the cellular level in both healthy and pathological tissue. However, real-timein vivo cellular imaging of the beating heart has not been fully established, mainly due to the difficulty of obtaining clear images through cycles of cardiac and respiratory motion. Here we report the successful recording of clearin vivo moving images of the beating rat heart by two-photon microscopy facilitated by cardiothoracic surgery and a novel cardiac stabiliser. Subcellular dynamics of the major cardiac components including the myocardium and its subcellular structures (i.e., nuclei and myofibrils) and mitochondrial distribution in cardiac myocytes were visualised for 4–5 h in green fluorescent protein-expressing transgenic Lewis rats at 15 frames/s. We also observed ischaemia/reperfusion (I/R) injury-induced suppression of the contraction/relaxation cycle and the consequent increase in cell permeability and leukocyte accumulation in cardiac tissue. I/R injury was induced in other transgenic mouse lines to further clarify the biological events in cardiac tissue. This imaging system can serve as an alternative modality for real time monitoring in animal models and cardiological drug screening, and can contribute to the development of more effective treatments for cardiac diseases.